Effect of Dietary Incorporation of Sugar Cane Molasses and Sexing on Broiler Performance and Carcass Characteristics - Mahmoud, Mutaz Saeed Babiker; Abdalla, Sara Abdalla AbdElrheem; Abdalla, Hydar Osman (Journal of Veterinary Medicine and Animal Production, 2021)
The study was conducted to evaluate the effect of partial replacement of sorghum grains by cane molasses on broiler performance and to compare the performance of male broiler chicks with unsexed one. A factorial (2 × 3) arrangement was used in a completely randomized design to study the effect of two sexing pattern (male and unsexed chicks) and three dietary levels of molasses (0, 10 and 24%) on broiler performance. A total of six treatments were employed and each treatment was replicated three times with six birds each. The experiment lasted for 42 days; the feed consumption, weight gain, and feed conversion ratio (FCR) were recorded. Carcass weight, weight of internal organs and carcass cuts were measured. Blood samples were collected for determination of cholesterol, triglycerides, total protein (TP) and potassium. The results revealed that significant improvement (P< 0.05) in feed consumption, body weight gain and FCR as the level of molasses increased. The feed consumed and the weight gain were significantly (P< 0.05) high in birds fed diets incorporated with 24% molasses. Males had better weight gain and feed consumption than unsexed birds while no differences in FCR. The highest value of serum TP and potassium were recorded in birds fed 24% molasses. Sexing had no significant effect (P˃ 0.05) on blood constituents. The weight of carcass, thigh, drumstick and breast were not affected by the experimental treatments. It is concluded that sugar cane molasses could be used as alternative energy source up to 24% in broiler diets without negative impact on performance. The males are advisable to be adopted for commercial broiler production than unsexed one.